A layerbased algorithm for the construction of connected dominating set in WSNs. (2015) - Zhang, Jun; Tang, Yong; Jun, Zhang; Wang, Wenyong
A smallsized virtual backbone is desirable to optimise the performance of wireless sensor networks. It is equivalent mathematically to the connected dominating set (CDS) in a graph. In this paper, we propose a layerbased algorithm for the construction of connected dominating set (LCDS). The algorithm divides the network into multiple layers according to the hop counts from a selected source node. Within each layer a local dominating set is constructed by greedy method in distributed manner to cover all the nodes in the next layer and the union of the dominating sets from all layers composes the CDS of the entire network. The experimental results show that LCDS algorithm generates a smaller CDS with less communication overhead even in high node density scenarios and its size varies relatively little with the rapid increase in node density.